Laporan Kasus: Penerapan Terapi Tertawa Dengan Menonton Video Wayang Cenk Blonk Pada Pasien Ansietas - farida mantul; Aini Rofikoh; Atika Jatimi (Indonesian Health Science Journal, 2024)
Hypertensive patients have physical complaints that cause anxiety in hypertensive patients characterized by restlessness, and difficulty sleeping. These symptoms indicate the presence of emotional and psychological stress. The purpose of this case study is to describe nursing care with the application of laughter therapy procedures in anxiety patients. The writing method uses a descriptive method with a nursing process approach consisting of assessment, diagnosis, planning, implementation and evaluation. The research subjects were 2 clients with anxiety nursing problems. Implementation results of the 4th day of Mrs. S still complains of difficulty sleeping and the objective data of Mrs. The S is not agitated, the client is not tense, and the Hars scale scores 22 problems are partially resolved. While Mrs. A is no longer complaining of difficulty sleeping and the objective data of Mrs. A is no longer restless, and the Hars scale scores 16 problems resolved. Conclusion After being given laughing therapy watching a wayang cenk blonk video to 2 clients with anxiety nursing problems, it was concluded that the level of anxiety decreased after being given laughing therapy watching a wayang cenk blonk video.